Pengaruh Laju Pertumbuhan Penduduk, Dependency Ratio Dan Tingkat Pendidikan Terhadap Pertumbuhan Ekonomi di Kota Langsa - Nurlaila Hanum; Miswar; Manovri Yeni; Mahdi; Radesi Bariaty (Kodepena Indonesia, 2022)
This study aims to determine the effect of population growth rate, dependency ratio and education level on economic growth in Langsa City in 2006-2021. The method of data collection in this research is done through a literature study, the data analysis method used is quantitative analysis using multiple linear regression analysis using the E-Views version 10. The results obtained by the equation Y = – 11.85942 – 0.322561 X1 + 0.284660 X2 + 0.195014 X3, based on the t-test the population growth rate has a negative and insignificant effect, the dependency ratio has a positive and significant effect and the level of education has a positive and insignificant effect on economic growth in Langsa City. Simultaneously the rate of population growth, dependency ratio and level of education have no significant effect on economic growth in Langsa City.